2011
DOI: 10.1016/j.ydbio.2011.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular development in the embryonic zebrafish hindbrain

Abstract: The brain is made of billions of highly metabolically active neurons whose activities provide the seat for cognitive, affective, sensory and motor functions. The cerebral vasculature meets the brain's unusually high demand for oxygen and glucose by providing it with the largest blood supply of any organ. Accordingly, disorders of the cerebral vasculature, such as congenital vascular malformations, stroke and tumors, compromise neuronal function and survival and often have crippling or fatal consequences. Yet, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 121 publications
3
81
0
Order By: Relevance
“…The first is the formation of a midline vessel from two lateral precursors. This resembles the way in which the midline basilar artery of the hindbrain forms from the two laterally positioned primordial hindbrain channels in zebrafish (Bussmann et al, 2011;Corti et al, 2011;Fujita et al, 2011;Ulrich et al, 2011). The second is 'vessel fusion', a unique process in which vessels coalesce by behaving like highly viscous liquid drops.…”
Section: Discussionmentioning
confidence: 86%
“…The first is the formation of a midline vessel from two lateral precursors. This resembles the way in which the midline basilar artery of the hindbrain forms from the two laterally positioned primordial hindbrain channels in zebrafish (Bussmann et al, 2011;Corti et al, 2011;Fujita et al, 2011;Ulrich et al, 2011). The second is 'vessel fusion', a unique process in which vessels coalesce by behaving like highly viscous liquid drops.…”
Section: Discussionmentioning
confidence: 86%
“…Most BA-forming sprout remnants are lost by 48 hpf; those that persist become avcs ( Fig. 4D,E; see Bussmann et al, 2011;Corti et al, 2011;Fujita et al, 2011;Fukuhara et al, 2014;Isogai et al, 2001;Ulrich et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the endothelial cellular bases of the intracerebral vascularization deficit of reck mutants (reck − ) we exploited the advantages of the hindbrain (Hb) vasculature as a model for cerebrovascular development, as we reported previously (Ulrich et al, 2011). The WT Hb harbors both extracerebral ( perineural) and intracerebral vessels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurospheres formed mainly from the proliferation of GFAP + radial glia cells that served as neural progenitors able to self-renew and differentiate after withdrawal of growth factors for three consecutive culture passages ( Figure S3E, arrowhead; data not shown). After 4 days in vitro in the absence of growth factors (Div4d), zebrafish neurospheres differentiated into all neural cell types: astrocytelike cells (GFAP + ) (Nielsen and Jørgensen, 2003), oligodendrocytes (Sox-10 + ) (Takada and Appel, 2010), and mature neurons (a-tubulin + ) (Ulrich et al, 2011) and expressed gene markers of several postmitotic neural cells (Figures S3F, arrowheads, and S3G). qRT-PCR analysis indicated that, during the course of neurosphere differentiation, dicer mRNA levels progressively declined, while miR-107 expression increased ( Figures 5A and 5B).…”
Section: Loss Of Mir-107 Function Promotes Hindbrain Neurogenesismentioning
confidence: 99%